The Effect of Income Level, Financial Literacy, and Lifestyle on Employee Spending Levels at PT. Hi-Lex Cirebon - Mia Auliah; Abdul Nasir; Syaeful Bakhri (International Journal of Business and Quality Research, 2026)
This study aims to analyze the influence of income level, financial literacy, and lifestyle on the level of expenditure of employees of PT. Hi-Lex Cirebon. This research is motivated by the increasing needs of employees' lives which are not always balanced with the ability to manage expenses. The research method uses a quantitative approach with a causal associative type. Data was obtained through questionnaires to 86 respondents who were selected using probability sampling using the random sampling method. Data analysis used multiple linear regression through t-test, F test, and determination coefficient. The results showed that the income level did not have a significant effect on the level of expenditure with a calculated t-value of 0.074 < 1.989 and a significance of 0.941 > 0.05. Financial literacy had a significant effect with a t-value of 2.127 > 1.989 and a significance of 0.036 < 0.05, while lifestyle had a significant effect with a t-value of 4.654 > 1.989 and a significance of 0.000 < 0.05. Simultaneously, the three variables had a significant effect on the level of expenditure with an F value of 21.285 > 2.70 and a significance of 0.000 < 0.05. An Adjusted R² value of 0.417 indicates that 41.7% of the variation in the level of expenditure can be explained by these three variables.